Moral Intelligence Enhancing Business Performance and Leadership Success - Lennick, Doug; Kiel, Fred (Pearson, 2005)
Through a combination of research, and original thought leadership, the authors demonstrate how the best performing companies have leaders who actively apply moral values to achieve enduring personal and organizational success. These individuals exhibit moral intelligence: a strong moral compass and the ability to follow it. Lennick and Kiel reveal how dozens of companies benefit from the moral intelligence of their leaders, help build specific moral competencies leaders need: integrity, responsibility, compassion, forgiveness, and more. This book also includes the new Moral and Emotional Competency Inventory (MECI): an indispensable metric to assess moral intelligence. Leaders with strong moral intelligence can build the trust and commitment that are the foundation of truly great businesses. Be one of those leaders, lead one of those companies, with Moral Intelligence.
Online resource; Title from title page (viewed May 3, 2005)
Keywords: Business ethics; Moral development; Success in business -- Moral and ethical aspects; Leadership -- Moral and ethical aspects; Morale des affaires; Développement moral; Succès dans les affaires; Aspect moral; Leadership; Aspect moral; Leadership; Moral and ethical aspects